First mature fruit description of Pietrosia laevitomentosa (Asteraceae) and its implications to the taxonomic position of the genus Pietrosia - Manole, Anca (Phytotaxa, 2015)
For the first time we describe the morphology and anatomy of mature achenes bearing fertile seeds of Pietrosia laevitomentosa, an endemic plant species in the Eastern Carpathians. The new diagnostic features of the genus Pietrosia justify its taxonomic recognition as separate from Andryala; those are the achene size (between 2.5 and 4.3 mm long), the deciduous pappus, the single-rimmed achene apex, the elongate exocarpic cells, the complete ring of mesocarpic sclerenchyma (up to 11-layered), and the number and localization of the vascular bundles (5 bundles, in the small ribs). Furthermore, our data may also serve to reconsider the species ecology and conservation strategies.